2011
DOI: 10.1016/j.str.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Ca2+ Inhibitory Mechanism of Drosophila Na+/Ca2+ Exchanger CALX and Its Modification by Alternative Splicing

Abstract: Summary The Na+/Ca2+ exchanger CALX promotes Ca2+ efflux in Drosophila sensory neuronal cells to facilitate light-mediated Ca2+ homeostasis. CALX activity is negatively regulated by specific Ca2+ interaction within its two intracellular Ca2+ regulatory domains CBD1 and CBD2, yet how the Ca2+ binding is converted to molecular motion to operate the exchanger is unknown. Here we report crystal structures of the entire Ca2+ regulatory domain CBD12 from two alternative splicing isoforms, CALX, 1.1 and 1.2, exhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 27 publications
4
37
0
3
Order By: Relevance
“…NMR studies reported a similarly extended shape for both the apo and bound states of CBD12, whereas Ca 2ϩ binding resulted in rigidified motions of CBDs (24). Moreover, x-ray crystallography revealed a nearly identical interdomain angle in the Ca 2ϩ -bound CBD12-NCX1-AD (18) and CBD12-CALX1.1 (22), meaning that the phenotype differences in the Ca 2ϩ -dependent activation or inhibition, exhibited by these diverse orthologs, cannot be explained by interdomain angle or distance (18).…”
Section: Mammalian Namentioning
confidence: 93%
See 4 more Smart Citations
“…NMR studies reported a similarly extended shape for both the apo and bound states of CBD12, whereas Ca 2ϩ binding resulted in rigidified motions of CBDs (24). Moreover, x-ray crystallography revealed a nearly identical interdomain angle in the Ca 2ϩ -bound CBD12-NCX1-AD (18) and CBD12-CALX1.1 (22), meaning that the phenotype differences in the Ca 2ϩ -dependent activation or inhibition, exhibited by these diverse orthologs, cannot be explained by interdomain angle or distance (18).…”
Section: Mammalian Namentioning
confidence: 93%
“…Ca 2ϩ binding is associated with CBD tethering and slow dissociation of "occluded" Ca 2ϩ from the Ca3-Ca4 sites (18). The structural properties of this interdomain module are very similar (if not identical) among diverse NCX orthologs and splice variants, exhibiting either positive, negative or no response to regulatory Ca 2ϩ (18,22). A slow dissociation of occluded Ca 2ϩ from regulatory sites may represent a physiologically relevant slow inactivation of NCX variants (I 2 state), observed in patch clamp experiments (12,23).…”
Section: Mammalian Namentioning
confidence: 99%
See 3 more Smart Citations